Shyness and groupism as prevalent cultural and attitudinal traits in learning English as a second language - Mohammad Lotfie, Maskanah (2007)
This paper explores the notion that learners’ social and cultural milieu are linked to language learning outcomes (Gardner, 1985). It investigates the perplexing problem of post-secondary students who cannot seem to achieve the necessary competence in using English verbally despite being in an environment where the target language is substantially used as the medium of instruction. The study focuses on three culture-related traits namely inwardness, shyness and groupism. Data collection involved 54 post-secondary Malay students and findings indicate that shyness and groupism play an important part in hindering students’ use of the target language. Students’ responses generally suggest that shyness and groupism decrease students’ oral participation in class. Students may make a conscious decision in not using the language as they are shy and the use may lead to a feeling of isolation from members of their in-groups.